Politiken kring svensk rymdverksamhet : Transkript av ett vittnesseminarium på Tekniska museet i Stockholm den 17 januari 2018 - Emanuel, Martin; Gärdebo, Johan; Wormbs, Nina (KTH, Urbana och regionala studier, 2018)
The witness seminar “Politiken kring svensk rymdverksam-het” (Politics relating to Swedish space activities) was held at Tekniska museet on January 17, 2018, and was led by Lennart Nordh, assisted by Johan Gärdebo. The seminar focused on the relationship between Swedish space activities and various forms of politics, from the 1960s until the 2000s. The discus-sants presented various definitions of politics, recurrently re-turning to the question whether or not Sweden ever had a comprehensive space policy or not. According to the partici-pants, Swedish space activities have been linked to their real or perceived contributions to other policy areas—research, technology, foreign policy, regional policy, and European in-tegration—but without a clear overriding political vision per-taining to space specifically. Initiatives were characterized as “management by opportunities,” which implies making full use of opportunities arising in- or outside of the space activi-ties. In addition to this, policy-makers, whether within the Swedish National Space Board, the Swedish Space Corpora-tion, or the Swedish space industry, have called upon allies in other European governments, organizations and industries, as well as individuals within the Swedish establishment to exert pressure on the Swedish Government at critical moments. On other occasions foreign pressure was exerted without any proposals from Swedish actors. It was noted that regional support for Kiruna has been important since Swedish space activities began in the 1960s, and the Esrange space range was established. The seminar identified several examples of how policy-makers within the Swedish space sector negotiated with governmental officials to gain support for projects and to expand the scope of space activities into other policy areas. Telecommunication, remote sensing and meteorology were discussed as the main areas in which space technology found operational use—although research and geographic surveying was also mentioned. Since the 1990s, the main changes ...